Challenging Issues Faced by Tailoring and Dressmaking Vocational Training Centres in Eldoret Municipality - Serem, Dorcas J (Nurture, 2008)
The main objective of this study was to investigate the challenging issues faced by church-based training institutions in Eldoret municipality who offer dressmaking and tailoring skills to the youth. Data was collected from 32 students and four teachers using questionnaire and from three managers and eight students who have graduated using interview schedule and analyzed using statistics. The study revealed that female trainees seek training to gain skill for paid or self-employment. It was also revealed that the teachers were qualified and some trainees dropped out of school because of marriage and teenage pregnancy. The study further revealed that students who sit for examinations perform well and appreciated attachment in the curriculum. The study recommends that institutions start a microfinance loan scheme to assist graduates who are interested in self-employment and vocational centres should include enterprise education in their curriculum to equip graduates with business skills.